Louisiana Humlebaek - Danmark : billedreportage. - Louisiana Museum of Modern Art, Humlebaek (Humlebaek : Louisiana Museum of Modern Art)
Calder, Alexander ; Francis, Sam ; Arman ; Dine, Jim ; Tinguely ; Long, Richard ; Hundertwasser ; Chagall, Marc ; Gabo, Naum ; etc.
boek